Is the Separation of State Attorneys the Key to Legal Reform in State Administrative Courts? - Sipahutar, Cornelius Samuel; Emha, Zidney Ilma Fazaada; Naelufar, Rizqan (Indonesian State Law Review, 2024)
The role of state attorneys in administrative justice has long been a topic of debate, particularly in the context of Indonesia’s State Administrative Court (PTUN). Currently, state attorneys serve as both legal representatives for the government and as the public prosecutor in administrative disputes. This dual function has raised concerns about potential conflicts of interest and inefficiencies in the judicial process. This research explores the concept of separating the roles of state attorneys in the PTUN as a potential bridge for legal reform, with the aim of improving impartiality, transparency, and efficiency in state administrative disputes. Using a normative juridical approach, the study examines the advantages and challenges of creating a clear distinction between the roles of government legal counsel and public prosecutors in administrative cases. The findings suggest that such a separation could reduce conflicts of interest, enhance fairness in the adjudication process, and promote a more balanced approach to administrative justice. However, the implementation of this reform faces practical challenges, such as institutional resistance and the need for legislative changes. The novelty of this research lies in its exploration of a structural reform within the Indonesian administrative justice system, offering a fresh perspective on improving the independence and credibility of state administrative courts. The urgency of this reform is emphasized by the growing need for a more transparent and efficient judicial system that can meet the demands of modern governance. This study contributes to the ongoing discourse on legal reform in Indonesia and provides recommendations for policymakers aiming to strengthen the administrative justice system.